Konstruksi Sosial Gender dalam Pola Asuh Orang Tua di Era Digital (Studi Kasus Pada Keluarga di Kota Makassar) - Sadriani, Andi (Peneliti.net, 2025)
This study aims to examine how social gender construction shapes parenting patterns in families in the digital era. A qualitative approach was used with an in-depth interview method with 10 married couples in Makassar City who have school-age children. Data were analyzed using thematic techniques, with steps ranging from interview transcription, data coding, identification of main themes, to interpretation based on the theory of social construction of gender. The results of the study show that although the digital era has changed many aspects of life, the division of roles in childcare is still dominated by traditional gender construction. Mothers remain the main party responsible for care, including accompanying children in online learning, monitoring gadget use, and searching for digital learning resources. Meanwhile, fathers tend to take a supporting or corrective role, which appears only when needed. These findings reflect how internalized gender norms continue to influence parenting practices in families, even amidst technological advances. The digital era, which should be an opportunity to encourage a more equal division of roles, actually shows a double burden for women. Therefore, transformative efforts are needed through gender education, father involvement campaigns, and family policies that support equal parenting so that families can become fair and adaptive spaces in the digital era.